2014
DOI: 10.1126/science.1252876
|View full text |Cite
|
Sign up to set email alerts
|

Using origami design principles to fold reprogrammable mechanical metamaterials

Abstract: Although broadly admired for its aesthetic qualities, the art of origami is now being recognized also as a framework for mechanical metamaterial design. Working with the Miura-ori tessellation, we find that each unit cell of this crease pattern is mechanically bistable, and by switching between states, the compressive modulus of the overall structure can be rationally and reversibly tuned. By virtue of their interactions, these mechanically stable lattice defects also lead to emergent crystallographic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
561
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 825 publications
(583 citation statements)
references
References 29 publications
2
561
0
Order By: Relevance
“…While most of the proposed origami-inspired metamaterials are based on 2D folding patterns, such as the miura-ori, [11][12][13][14][15][16][17] the square twist 18 and the box-pleat tiling, 19 it has been shown that cellular structures can be designed by stacking these folded layers, 13 or assembling them in tubes. [20][21][22][23] Furthermore, by taking inspiration from snapology 24,25 -a modular origami technique -a highly reconfigurable 3D metamaterial assembled from extruded cubes has been designed.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the proposed origami-inspired metamaterials are based on 2D folding patterns, such as the miura-ori, [11][12][13][14][15][16][17] the square twist 18 and the box-pleat tiling, 19 it has been shown that cellular structures can be designed by stacking these folded layers, 13 or assembling them in tubes. [20][21][22][23] Furthermore, by taking inspiration from snapology 24,25 -a modular origami technique -a highly reconfigurable 3D metamaterial assembled from extruded cubes has been designed.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of this coupling are seen in both naturally occurring scenarios, such as intestinal villi and pollen grains (4,5), and find use in man-made structures such as programmable metamaterials (6)(7)(8)(9). When these shells have multistable configurations, the transition between them is opposed by geometrically enhanced rigidity resulting from the dominant stretching energy.…”
mentioning
confidence: 99%
“…For example, rigid origami systems are defined as those having a kinematic deformation mode in which movement is concentrated along the fold lines, whereas the panels remain flat (20,21). Among various rigid folding patterns, the Miura-ori has attracted attention for its folding characteristics (22,23), elastic stiffness properties beyond rigid folding (24,25), geometric versatility (26,27), and intrinsic material-like characteristics (28,29).…”
mentioning
confidence: 99%